The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1002/lary.22374
|View full text |Cite
|
Sign up to set email alerts
|

Does mucosal remodeling in chronic rhinosinusitis result in irreversible mucosal disease?

Abstract: Mucosal remodeling in the sinuses is a recently described phenomenon in which the mucosa undergoes potentially irreversible changes as a result of ongoing underlying inflammatory processes. Research into remodeling that occurs in the bronchial airways in asthmatic patients has led to modification of asthma treatment guidelines. However, remodeling in the sinuses has still not led to changes in current medical or surgical management of chronic rhinosinusitis. Upper airway remodeling constitutes a new area of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 51 publications
1
25
1
5
Order By: Relevance
“…Increased surgery could lead to, or be the consequence of, mucosal remodeling. Indeed, such patients may have developed "dysfunctional" frontal sinuses as suggested by Bassiouni et al 17 Our findings regarding AERD are in keeping with Georgalas et al, 11 but in contrast to Tran et al 16 and Schlosser et al, 18 who found no association between AERD and failure of the EMLP in cohorts of 44 and 77 patients, respectively. The association of AERD with failure may be related to the more aggressive recurrence of polyps in this specific cohort.…”
Section: Discussionsupporting
confidence: 87%
“…Increased surgery could lead to, or be the consequence of, mucosal remodeling. Indeed, such patients may have developed "dysfunctional" frontal sinuses as suggested by Bassiouni et al 17 Our findings regarding AERD are in keeping with Georgalas et al, 11 but in contrast to Tran et al 16 and Schlosser et al, 18 who found no association between AERD and failure of the EMLP in cohorts of 44 and 77 patients, respectively. The association of AERD with failure may be related to the more aggressive recurrence of polyps in this specific cohort.…”
Section: Discussionsupporting
confidence: 87%
“…Another hypothesis as to why the EMLP is successful in resolving persistent symptoms of CRS is supported by two recently published literature reviews into the failure of ESS, which dealt with the concept of inflammatory load and mucosal remodeling . Intraoperatively, the EMLP allows the majority of the frontal sinus to be accessed, with removal of polypoid mucosa and eosinophilic mucous.…”
Section: Discussionmentioning
confidence: 99%
“…839,840 Sinonasal mucosal remodeling, at times irreversible, can occur. 841,842 The varied medical therapies aimed at treatment of CRSsNP, including antibiotics and systemic corticosteroids, can also cause serious complications and add morbidity to the disease. [843][844][845][846][847] VIII.…”
Section: Viif Crssnp: Complicationsmentioning
confidence: 99%